Inequalities in Utilisation and Provision of Dental Services: A Scoping Review. (20th October 2021) - Ghanbarzadegan, A; Bastani, P; Luzzi, L; Brennan, D
Abstract: Background: To explore the main determinants of inequality in both provision and utilisation of dental services in OECD countries. Methods: Four databases were searched up to 8 Aug 2020 applying the relevant keywords. Thematic analysis was used for synthesizing and extracting data. Trend analysis was applied to determine the trends of the inequality determinants. Results: Thematic analysis led to 53 sub-sub-themes, 13 sub-themes and 6 main-themes. The main themes represent the main inequality determinants for both utilisation and provision of dental services. The streamgraph illustrates that fewer studies have been conducted on social and cultural determinants, and in almost all determinants the trend of published articles has been increasing since 2007 except for health policies. Conclusions: Inequality in the utilisation and provision of dental services is addressed by various factors including individual, social, cultural and economic determinants, health policies and availability of services. The first four determinants are related to utilisation and the last two are related to the provision of services. All these aspects must be considered to reduce inequality in dental services. Key messages: Service Utilisation, Provision and access to service int the dental literature should be distiguished and redefined. Researchers and policymakers should pay attention simultaneously to all structured determinants of inequality in the dental services.